Career adaptability and correlating factors among secondary vocational nursing students in China - Xiang, Yuhe; Li, Lin; Yang, Qin; Fang, YiQian; Xu, Wenbin; Ding, Xing; Yang, Qian (Frontiers in Public Health, 2024)
Background Career adaptability significantly affects college students’ career happiness in the future, and it is essential to make a detailed evaluation of its correlation for making a targeted intervention plan. However, the applicability of occupational adaptability to secondary vocational nursing students is still an unexplored field in academic research. Objective This study aimed to investigate the current situation of career adaptability and its influencing factors on secondary vocational nursing students in medical schools. Methods A total of 1,414 secondary vocational nursing students from three secondary colleges and universities in Southwest China from July 2022 to September 2022 were selected for the survey. A questionnaire was used to assess secondary vocational nursing students’ sociodemographic, Career Adaptability, Psychological Control Sources, and the Meaning in Life. Statistical analyses were performed using Pearson’s correlation analysis, t-test, analysis of variance and multiple. Results Secondary vocational nursing students scored (51.03 ± 9.64) for the meaning in life, (81.46 ± 25.39) for psychological control sources, and (94.12 ± 15.55) for career adaptability. Career resilience was significantly and positively correlated with the opportunity and internal control factors of psychological control sources (r = 0.091, −0.488, p < 0.01); and career adaptability was significantly and positively correlated with the sense of seeking meaning and possessing meaning factors of sense of meaning in life (r = 0.725, 0.734, p < 0.01); Multiple linear regression analysis revealed that academic performance, mother’s educational level, search for meaning, sense of meaningfulness, opportunities, and internal control entered the regression equation (p < 0.05), explaining 64% of the total variance. Conclusion The overall career adaptability of secondary vocational nursing students is at a moderately high level, with significant individual differences closely correlated with locus of control, meaning in life, and career adaptability. Nursing educators can provide targeted intervention measures based on influencing factors to promote the development of secondary vocational nursing students’ career adaptability, enabling them to better adapt to future clinical work.